Derecho del clérigo a la buena fama [tesis doctoral] - Martínez, Francisco José Campos (Revista española de derecho canónico, 2023)
Review of the book by the American civil and canon lawyer, Michael Joseph Mazza, where he has made this relevant issue the main theme of his recent doctoral thesis defended at the Pontifical University of the Holy Cross (Rome) under the title: The Right of a Cleric to Bona Fama. The work focuses on the origins, development and current state of the right to good fame, particularly as it pertains to the life of clerics.